Evaluation Of Diploma In Family Medicine Ensuring Quality Through CIPP Model - Rahila Ali; Asif Farooqui; Arshia Samin Naqvi; Jawaid Usman (ziauddin University, 2024)
Background: To ensure quality of Diploma in Family medicine (DFM). An evaluation was conducted to determine the components and outcomes of the course for further development of the program. Methods: A Cross-sectional study was conducted with 15 students of three batches of DFM. Data collection form was designed on CIPP evaluation approach. It was used to collect information regarding goals and objectives, implementation strategy, satisfaction of instructor and trainees and impact of the program on the target population Descriptive measures (frequency and percentage distributions) were used to analyze the data on SPSS 19. Results: Majority (92%) were satisfied with the course content, organization, learning environment and teaching methods of Family medicine rotation. Most of the respondents (92%) were also satisfied with learning recourses accessible and assessment methodologies employed for ongoing assessment. They found 'the atmosphere conducive for learning' ,'the rotations were a good experience, well organized with learning objectives provided at all rotations' some suggestions made by students for improvement of the course 'were teaching should be more interactive and more opportunity should be provided to participate with consultants' The top rated rotations were dermatology, emergency medicine, ENT and orthopedics; where organizational learning environment and quality of delivery were considered as the best parts. Conclusion: The program was found successful in achieving its broad objectives. The graduating students found the training effective in enhancing team building abilities, independent thinking, analytical and problem solving skills and professional development. They were very satisfied with the administrative support (67%), infrastructure of the department (33%) and guidance by supervisors (67%). Key Words: Evaluation, Family medicine, Diploma